Daily intake of Lactobacillus gasseri CP2305 ameliorates psychological premenstrual symptoms in young women: A randomized, double-blinded, placebo-controlled study - Nishida, Kensei; Sawada, Daisuke; Yasui, Toshiyuki; Kuwano, Yuki; Rokutan, Kazuhito (Journal of functional foods, 2021)
[Display omitted] •Effects of Lactobacillus gasseri CP2305 on premenstrual symptoms were investigated.•CP2305 tablets reduced self-reporting of “depressed mood” by healthy young women.•Water retention-related symptoms unchanged with CP2305 but reduced in placebo group.•CP2305 tablets affect changes in salivary reproductive hormones in the luteal phase. Lactobacillus gasseri CP2305 (CP2305) ameliorates stress-induced symptoms in young adults. In this study, we evaluated the effects of CP2305 on the premenstrual symptoms of healthy young women. Fifty-six women ingested CP2305 or placebo tablets over the course of six menstrual cycles. The CP2305 group reported fewer premenstrual symptoms than the placebo group, particularly psychological symptoms, such as depressed mood and anxiety. Whereas water retention-related physical symptom scores, such as those for breast tenderness and swelling, were reduced in the placebo group, they remained unchanged in the CP2305 group. In addition, significant differences were observed in the changes from baseline levels of salivary estradiol and progesterone in the luteal phase between the two groups, resulting in sustained elevated levels of reproductive hormones in the CP2305 group. Therefore, daily intake of CP2305 tablets might improve the premenstrual psychological symptoms of healthy young women in association with changes in reproductive hormone levels.